EFFECTIVE DIFFERENT TERM CROP ROTATIONS ARE IN MODERN AGRICULTURE - Бойко, П. І.; Коваленко, Н. П.; Опара, М. М. (Scientific Progress & Innovations, 2014)
Strategy of improvement and innovation of structure of sowing areas and scientifically reasonable crop rotations is considered taking into account ground-climatic terms and specialization of economies. It is set that high-performance and environmentally sounds different term: shot term 3–4–5-fields and long term 6–10-fields grain, grain-growing, grain-par-growing, cultivated, forage crop rotations with the wide limits of satiation grain, technical and forage crops. It is discovered that the effect of crop rotation rises for the increase of variety of agricultural cultures and length of rotary press, that it is needed to take into account at development of projects of organization of the use of land for providing of eco-economical ground of crop rotations and organization of lands, their composition and maintenance.